Wrestlers` health - biological, behavioural and axiological aspects - Sokolowski, M.; Kaiser, A.; Czerniak, U.; Tomczak, M.; Breczewski, G. (Archives of Budo, 2012)
Background and Study Aim: The aim of this paper is to analyse health potential of wrestlers from the wrestling national team. The analysis is based on body composition, health valuation and implementation of selected health behaviours. Material and Methods: The research was carried out in the Wrestling Centre in Poznan, Poland in 2010. It involved twenty members of the Polish national wrestling team (ten girls and ten boys participating in the European Qualifications for the 1st Youth Olympic Games (YOG) in Singapore. The average age of the sample group was 16.5 years for boys (M=16.50; Sd=0.53) and for girls 15.6 years (M=15.60; Sd=0.52). Competitors underwent anthropometrical and body composition examination (Bioelectrical Impedance Analysis - BIA). Evaluation made use of the List of Personal Values (LoPV), International Physical Activity Questionnaire (IPAQ), as well as an authorial questionnaire. Results: Mean body mass index of girls and boys, and their body composition are within standard values. Yet, among boys tissue composition is less varied than among girls. What is more, in several cases girls' fat mass exceeded standard values. Young sportsmen and sportswomen appreciate health, however, it is rarely a superior value for them. Though smoking is not a problem, these young people tend to experiment with intoxicating substances, which is far more disturbing. Conclusion: Physical activity regulating energetic balance may be an efficient method in preventing fat accumulation by wrestling girls and boys. In concern about competitors' health at present and in the future it is crucial to include health education into their sport training, which not only will allow them to achieve momentary sport success, but also may help to shape their long-term attitudes towards health and fitness.